The Influence of Internal Employer Branding and Leadership Styles in Increasing Employee Engagement: The Mediating Effect on Employee Experience - Novita, Renny; Hermina, Nurul (Almana : Jurnal Manajemen dan Bisnis, 2025)
The hospitality industry, particularly 5-star hotels at the pinnacle of this sector, heavily relies on exceptional service quality standards to uphold the brand reputation, customer satisfaction, and overall Customer Experience (CX). Achieving these high standards largely depends on Employee Engagement (EE), as well as employee satisfaction and retention, given that employees serve as the hotel's frontline brand ambassadors. However, the industry—including the 5-star Hotel X in Bali—faces a higher employee turnover rate than other sectors. One of the ways that Hotel X fosters employee engagement (EE) is by implementing internal employer branding (IEB) initiatives. This study aims to measure the effect of Internal Employer Branding (IEB) and Leadership Style (LS) —a key factor influencing employee turnover—on Employee Engagement (EE), with Employee Experience (EX) acting as a mediating variable. The research employs Partial Least Square Structural Equation Modeling (PLS-SEM) analysis using a saturated sample of 252 respondents. Hypothesis testing results indicated that 4 out of 5 direct effect hypotheses positively affect their latent variables, and 1 of 2 specific indirect effect (mediation) hypotheses directly impact Employee Engagement (EE). The findings suggest that Employee Experience (EX) substantially mediates internal employer branding (IEB) and Employee Engagement (EE). However, Leadership Style (LS) proved to be more effective in directly enhancing Employee Engagement (EE) than through Employee Experience (EX).